Epitaxial growth of MgFe2O4 (111) thin films on sapphire (0001) substrate - Gupta, R. K.; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2011)
Pulsed laser deposition technique is used to fabricate thin films of MgFe2O4 on sapphire substrate. X-ray diffraction patterns show that films are epitaxial along (lll) direction on c-axis oriented sapphire. The observation of six fold symmetry in phi scan for the film suggests the presence of twinned in-plane alignments. The presence of magnetic hysteresis loop at room temperature indicates the ferromagnetic behavior of the film. The coercive field of 742 Oe and remnant magnetization of 151 emu/cm(2) is observed at room temperature. The coercive field and remnant magnetization decrease with increase in temperature. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Epitaxial thin films; MgFe2O4; Pulsed laser deposition; Ferromagnetic